2015
DOI: 10.1038/jid.2015.89
|View full text |Cite
|
Sign up to set email alerts
|

Acne Treatment Based on Selective Photothermolysis of Sebaceous Follicles with Topically Delivered Light-Absorbing Gold Microparticles

Abstract: The pathophysiology of acne vulgaris depends on active sebaceous glands, implying that selective destruction of sebaceous glands could be an effective treatment. We hypothesized that light-absorbing microparticles could be delivered into sebaceous glands, enabling local injury by optical pulses. A suspension of topically applied gold-coated silica microparticles exhibiting plasmon resonance with strong absorption at 800 nm was delivered into human pre-auricular and swine sebaceous glands in vivo, using mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 27 publications
2
79
0
Order By: Relevance
“…Further, the imaging technologies illustrated that skin areas with active acne elements and an intact surface did not influence delivery of GMPs and that delivery of GMPs was similar in acne patients and healthy participants. RCM illustrated laser‐mediated thermal effect around NSOs containing GMPs from skin surface to dermo‐epidermal junction, indicating that not only the deeper parts of the pilosebaceous units, but also the upper infundibular portion are affected by the heat generated after laser exposure of GMPs .…”
Section: Discussionmentioning
confidence: 99%
“…Further, the imaging technologies illustrated that skin areas with active acne elements and an intact surface did not influence delivery of GMPs and that delivery of GMPs was similar in acne patients and healthy participants. RCM illustrated laser‐mediated thermal effect around NSOs containing GMPs from skin surface to dermo‐epidermal junction, indicating that not only the deeper parts of the pilosebaceous units, but also the upper infundibular portion are affected by the heat generated after laser exposure of GMPs .…”
Section: Discussionmentioning
confidence: 99%
“…These particular 150 nm GNSs were selected because they have been demonstrated to penetrate into hair follicles easily after vibratory massage. The GNSs are certified as medical device CE 612960 and approved for clinical use and topical treatment of acne vulgaris combined with selective photothermolysis . in vivo studies have shown that these GNSs are not retained in swine skin 1 month after vibratory massage into the skin and that uptake in other organs is negligible since it is 74 times lower than the established safety threshold .…”
Section: Methodsmentioning
confidence: 99%
“…The GNSs are certified as medical device CE 612960 and approved for clinical use and topical treatment of acne vulgaris combined with selective photothermolysis . in vivo studies have shown that these GNSs are not retained in swine skin 1 month after vibratory massage into the skin and that uptake in other organs is negligible since it is 74 times lower than the established safety threshold . The GNS is supplied in glass vials in a 25% solution in quantities of 1 mL (Sebacia Microparticles, Sebacia Inc., Duluth, Georgia) suspended in a combination of ethanol (54%), polysorbate 80 (1%) and diisopropyl adipate (20%).…”
Section: Methodsmentioning
confidence: 99%
“…IPL efficacy did not appear to be significantly enhanced when combined with PDT [62, 6468]. IPL’s efficacy may be due in part to its longer wavelengths, which have the ability to produce selective photothermolysis of sebaceous glands; sebum has an absorption peak at 1210 nm [69]. LPDL, which uses a wavelength of 595 nm, was more effective at decreasing ILC in patients with mild to severe acne when combined with PDT (67% vs. 100%) [70, 71].…”
Section: Resultsmentioning
confidence: 99%